(untitled) (Journal of history, 2019)
In this article, the author pays special attention to the code of laws of the Kazakh people, Khasim Kasym called «The bright path of Kasym Khan», based on ancient rules, customs and traditions. The content of laws is analyzed from the point of view of law and other related areas of the humanities. The author also draws attention to the relevance of this topic in modern times. Therefore, the article presents parallels with the realities of the present. At the end of the article, the author refers to the role of Kasim Khan in the history of the statehood of the Kazakh people and the significance of its set of laws in the history of the formation of the laws of the Kazakh steppe.